Presentation is loading. Please wait.

Presentation is loading. Please wait.

Factorisation. ab + ad = a( b +……... Multiplying Out Brackets reminder. (1) 6 ( x + 3 ) (2) 3 ( 2x + 5 ) (3) 4 ( 6x + 7 ) (4) 9 ( 3x + 9 ) (5) 2 ( 3x.

Similar presentations


Presentation on theme: "Factorisation. ab + ad = a( b +……... Multiplying Out Brackets reminder. (1) 6 ( x + 3 ) (2) 3 ( 2x + 5 ) (3) 4 ( 6x + 7 ) (4) 9 ( 3x + 9 ) (5) 2 ( 3x."— Presentation transcript:

1 Factorisation. ab + ad = a( b +……..

2 Multiplying Out Brackets reminder. (1) 6 ( x + 3 ) (2) 3 ( 2x + 5 ) (3) 4 ( 6x + 7 ) (4) 9 ( 3x + 9 ) (5) 2 ( 3x + 4 ) (6) 8 ( 5x + 7 ) =6x+18 6x+15 24x+28 27x+81 6x+8 40x+56 = = = = = Multiply out the brackets below:

3 Putting The Brackets Back In. In maths it is not only important to be able to multiply out brackets but also to be able to put the brackets back. This process is called FACTORISATION. How to factorise: Consider the expression below : 6a + 12Can you think of a number that divides into both 6 and 12 ? 6 is a common factor. Now take 6 outside the bracket and work out what goes inside the bracket. = 6 (a+2 ) Now the expression is factorised.

4 Further Examples. Now factorise the following expressions: (1) 5 x + 10 =5 (x+2 ) (2) 7 x + 21 =7 (x+3 ) (3) 6 x - 9 =3 (2 x-3 ) (4) 15 x - 20 =5 (3 x-4 ) (5) 24 x + 8 =8 (3 x+1 )

5 What Goes In The Box ? Factorise the following expressions: (1) 6x + 12 = (2) 9x - 18 = (3) 8x + 12 = (4) 7x - 21 = (5) 10x + 15 = 6( x + 2 ) 9( x - 2 ) 4( 2x + 3 ) 7( x - 3 ) 5( 2x + 3 )

6 Multiplying Out Brackets Reminder 2 (1) 3t ( 2t + 6 ) =6t 2 +18t (2) 4w ( 3w - 7 ) =12w 2 - 28w (3) 5a ( 2a + 9 ) =10a 2 +45a (4) 2z ( 5z - 8 ) =10z 2 -16z Multiply out the brackets below:

7 Harder Factorisation. In the example below there is more than one term to be removed from the bracket. Factorise : 3ab – 12ad Remove any numbers first. = 3( ab–4ad ) Now remove any letters. = 3a ( b–4d ) The expression is now fully factorised.

8 Further Examples. Factorise the following expressions: (1) 5wg – 10 wm = 5 (wg–wm ) = 5w( g – m ) (2) 16xy – 8xw = 8 (2xy– xw ) = 8x( 2y – w ) (3) 9ab + 12bc = 3 (3ab+4bc ) = 3b( 3a+4c ) (4) 6x 2 + 9 xy = 3 (2x 2 +3xy ) = 3x( 2x+3y )

9 What Goes In The Box ? Factorise the following expressions: (1) 6ag – 18 af (2) 7x 2 w + 28xy = 6( ag -3 af ) = 6a( g - 3 f ) = 7(x 2 w + 4 xy ) = 7x( xw +4y )


Download ppt "Factorisation. ab + ad = a( b +……... Multiplying Out Brackets reminder. (1) 6 ( x + 3 ) (2) 3 ( 2x + 5 ) (3) 4 ( 6x + 7 ) (4) 9 ( 3x + 9 ) (5) 2 ( 3x."

Similar presentations


Ads by Google